Studying the effect of Gold Nanoparticles on some bacterial species isolated from surgical wound infections (Journal of Pharmaceutical Negative Results, 2022)
The process of synthesis of gold nanoparticles biologically is a safe, environmentally friendly and inexpensive method and had an effect on the most common bacterial species in surgical inflammation, as the gold particles were synthesized in a biological way and no toxic substance was used, as secondary metabolites (K. pneumoniae) as a reducing agent of HAuCL4.4H2O chloric acid to gold nanoparticles. Characterization of gold nanoparticles was carried out using ultraviolet spectroscopy, which showed that the absorption peak was at 572 nm. The infrared absorption spectrum showed several peaks ranging between (600-4000) evidence of the interference of gold nanoparticles with the particles contained in the bacterial suspension (leachate), and transmission electron microscopy (TEM) images showed that gold nanoparticles were spherical in shape, and X-ray diffraction examination showed that they are particles of spherical shape. Nano-gold compared to the reference card (ICDD card No.03-065-2870).